Comparison of performance characteristics of desiccant coated air-water heat exchanger with conventional air-water heat exchanger – Experimental and analytical investigation. (15th October 2017) - Sun, X.Y.; Dai, Y.J.; Ge, T.S.; Zhao, Y.; Wang, R.Z.
Abstract: In this study, the heat and mass transfer characteristics of desiccant coated heat exchanger (DCHE) and conventional heat exchanger are compared by experiments. A general-purpose test platform is built to test and compare the characteristics above. Based on the designed experimental setup, two heat exchangers of different depths of fins conventional/desiccant coated are experimentally investigated and compared with the given performance evaluation standards. In addition, parametric influences of inlet air velocity, hot water temperature and cycle time are analysed. Experimental results show that compared with the conventional heat exchanger, the heat transfer capacity of DCHE is reduced by 30% because of the heat resistance produced by desiccant coating. Pressure drop and Euler number are both increased by 60% approximately for the same reason. Doubling the depth of fins increases the average moisture removal by 40% and COPth by 10%, without changing the other structure parameters. Highlights: An experimental setup is built to test the characteristics of desiccant coated heat exchanger. Performance evaluation standards of heat and mass transfer, coefficient of performance and pressure drop are determined. Heat transfer capacity of DCHE is reduced by 30% compared with conventional one. With double DCHE depth of fins, mass transfer capacity increases by 40%, while coefficient of performance increases by 10%. Pressure drop and Euler number of DCHE both increase by 60% approximately compared with conventional one.